Serological surveillance reveals a high exposure to SARS-CoV-2 and altered immune response among COVID-19 unvaccinated Cameroonian individuals. - Arlette Flore Moguem Soubgui; Wilfred Steve Ndeme Mboussi; Loick Pradel Kojom Foko; Elisée Libert Embolo Enyegue; Martin Luther Koanga Mogtomo (Public Library of Science (PLoS), 2024)
Surveillance of COVID-19/SARS-CoV-2 dynamics is crucial to understanding natural history and providing insights into the population's exposure risk and specific susceptibilities. This study investigated the seroprevalence of SARS-CoV-2 antibodies, its predictors, and immunological status among unvaccinated patients in Cameroon. A multicentre cross-sectional study was conducted between January and September 2022 in the town of Douala. Patients were consecutively recruited, and data of interest were collected using a questionnaire. Blood samples were collected to determine Immunoglobin titres (IgM and IgG), interferon gamma (IFN- γ) and interleukin-6 (IL-6) by ELISA, and CD4+ cells by flow cytometry. A total of 342 patients aged 41.5 ± 13.9 years were included. Most participants (75.8%) were asymptomatic. The overall crude prevalence of IgM and IgG was 49.1% and 88.9%, respectively. After adjustment, the seroprevalence values were 51% for IgM and 93% for IgM. Ageusia and anosmia have displayed the highest positive predictive values (90.9% and 82.4%) and specificity (98.9% and 98.3%). The predictors of IgM seropositivity were being diabetic (aOR = 0.23, p = 0.01), frequently seeking healthcare (aOR = 1.97, p = 0.03), and diagnosed with ageusia (aOR = 20.63, p = 0.005), whereas those of IgG seropositivity included health facility (aOR = 0.15, p = 0.01), age of 40-50 years (aOR = 8.78, p = 0.01), married (aOR = 0.21, p = 0.02), fever (aOR = 0.08, p = 0.01), and ageusia (aOR = 0.08, p = 0.01). CD4+, IFN-γ, and IL-6 were impaired in seropositive individuals, with a confounding role of socio-demographic factors or comorbidities. Although the WHO declared the end of COVID-19 as a public health emergency, the findings of this study indicate the need for continuous surveillance to adequately control the disease in Cameroon.